2020
DOI: 10.9734/jsrr/2021/v26i1230339
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacology of Acorus calamus L. among Indigenous Communities of Ganderbal District in Kashmir

Abstract: The present study was undertaken to collect the information regarding ethnomedicinal practices of Acorus calamus and data were collected by using a well-designed interview schedule from local herbal heelers called “Hakeems, Bohris”  experts in the Ayurvedic and Unani medicine, local collectors. The results indicated that the main ailment categories that are treated by Acorus calamus include skin diseases, renal/urinary disorders, muscular/skeletal disorders, respiratory diseases, eye diseases, fever and others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…For example, Zhang et al (2021) identified that in China, their sample of college students had relatively low levels of disaster literacy, but factors such as disaster experience, disaster training experience, and family disaster preparedness influence college students' disaster literacy. Similar findings have been found in both Indonesia (Aksa et al 2020) and India (Bhat et al 2017). Particularly in Indonesia, there was a significant relationship between earthquake knowledge and risk perception (Aksa et al 2020).…”
Section: College Students' Disaster Preparedness and Literacysupporting
confidence: 86%
See 1 more Smart Citation
“…For example, Zhang et al (2021) identified that in China, their sample of college students had relatively low levels of disaster literacy, but factors such as disaster experience, disaster training experience, and family disaster preparedness influence college students' disaster literacy. Similar findings have been found in both Indonesia (Aksa et al 2020) and India (Bhat et al 2017). Particularly in Indonesia, there was a significant relationship between earthquake knowledge and risk perception (Aksa et al 2020).…”
Section: College Students' Disaster Preparedness and Literacysupporting
confidence: 86%
“…A major theme that emerged during the qualitative analysis of the publications in our review was college students' understanding of disasters (e.g., disaster literacy) and their preparedness for disasters (e.g., Bhat et al 2017;Contreras 2014). Several studies examined the diverse impact of various factors on students' perceptions of disaster risk, emphasizing the imperative need for tailored strategies and interventions in the realm of disaster risk management (Aksa et al 2020;Mızrak and Aslan 2020;Zhang et al 2021).…”
Section: College Students' Disaster Preparedness and Literacymentioning
confidence: 99%
“…The questionnaire was designed to assess students' knowledge and awareness about disaster preparedness. The questionnaire has six sections -demographic, understanding of preparedness, disaster awareness, perception of roles and responsibilities, preparedness actions, and access to information (Community of Accredited Online Schools) (Tanner and Doberstein, 2015;Bhat et al, 2017;Rohith et al, 745-753). The internal consistency reliability check produced an alpha coefficient (Cronbach's alpha) of 0.91 (greater than 0.7), indicating an acceptable correlation between the items of the questionnaire, and its content validity was further examined by five (5) professors and researchers related to the field.…”
Section: Methodsmentioning
confidence: 99%
“…Disasters like floods, earthquakes, fires, typhoons and the like pose a serious threat to people (Matunhay, 2018). In this context, disaster education, which includes education on disaster risks, mitigation, and preparedness strategies, is one approach to reducing the negative consequences of disasters (Bhat, et al, 2017).The Asia Pacific region is the most disaster-prone and most disaster-affected in the world (Smith, 2003). In terms of disaster risk, the Philippines ranked third among all of the countries with the highest risks worldwide according to the World Risk Report 2018, with an index value of 25.14% (UNDRR, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation